Employees' Workplace Well-Being and Organizational Citizenship Behavior of Private Education in Ilocos Norte, Philippines - Abun, Damianus; Pellogo, Restita B.; Magallanes, Theogenia; Sapinoso, Melody Luz, M.; Encarnacion, Mary Joy (Technium Social Sciences Journal, 2021)
The study intended to determine the effect of workplace well-being particularly hedonic and eudemonic well-being on the organizational citizenship behaviour of the employees. To support the theoretical foundation of the study, related literature was reviewed. The respondents of the study were all employees from the Divine Word Colleges in the Ilocos region. The study applied descriptive assessment and correlational research design. To analyse the data, the weighted mean and Pearson r correlation was used. The study found that the workplace well-being of employees and their organizational citizenship behaviour were considered high and it was also found that there is no correlation between the workplace well-being and the organizational citizenship behaviour of the employees. Therefore, the hypothesis of the study, that there is a correlation between workplace well-being and organizational citizenship behaviour is rejected. This finding contributes to a wider discussion on the effect of workplace well-being on organizational citizenship behaviour.